The Impact of Underdevelopment on Economic Planning - Watson, Andrew M.; Dirlam, Joel B. (Quarterly Journal of Economics, 1965)
I. The background to planning: development in the preplanning period, 168. — II. Establishing a “Development Board”: the centralization of aid negotiation, 170. — III. Pressure for more planning, 172. — IV. The planner's dilemma: long-range planning or implementation, 174. — V. Constraints on planning, 176. — VI. The scope of development plans, 178. — VII. Implementation, 183. — VIII. Major obstacles resulting from underdevelopment, 186. — IX. Conclusion: the orientation of planning, 192.